Analysis of Organization X Problems Through Diagram Fishbone and Implementation of Plan - Do - Check - Action - Since Novayanti Manik; Cholichul Hadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
CyclePlan-Do-Check-Action(PDCA cycle) is part ofcontinuous improvementwhich was initiated by W. Edwards Deming. The PDCA cycle emphasizes that every management action can be improved by carefully implementing the following work sequence:plan, do, check, actionThe data collection process began with an analysis of the problems experienced by the kitchen work unit. However, three kitchen supervisors reported that the problem they were facing was confusion over menu variations. This issue was then collectively examined for its underlying causes using a 5-point analysis.Whywith the next action plan. After usingtool 5 why, tracing the root cause of the problem felt like something was missing, so that when looking at the next action plan, it still seemed inadequate. Therefore, we tried usingtoolanother isfishbone diagram. FishboneThe diagram turned out to produce various root causes, even some things that were thought to be the main problem turned out to be the root cause of the main problem. Confusion in the menu variations was caused by 5 things consisting ofmanpower, machine, method, material And environmentwhich can be seen in detail in the partsfishbonePDCA diagram is a work sequence that can be used after knowing the root cause of the problem faced by organization X. The plans that will be carried out and the results that can be seen are based on observations and results from the table.checkweekly every two months.